Interrelation of Physicochemical and Biochemical Parameters of Oral Fluid with Periodontal Pathology in Children with Distal Occlusion and Impaired Respiratory Function - Lykhota, К. М.; Vataha, К. А. (Actual Dentistry, 2025)
Introduction. Distal occlusal (DO) anomaly is a common dentoalveolar anomaly in children, significantly affecting the development of the dentofacial system and chewing function. Its high prevalence, according to various epidemiological data, reaches 20–30% among the pediatric population, making its diagnosis and correction a relevant issue. The formation of distal occlusion is often associated not only with genetic predisposition but also with harmful habits and functional disorders, particularly respiratory pathology. Narrowing of the airways due to anatomical or physiological limitations during craniofacial development, for example, in mandibular retrognathia, can directly cause impaired external respiration. Chronic mouth breathing, compensating for nasal breathing difficulties, leads to several negative consequences for the oral cavity: changes in salivary pH, reduced protective and self-cleaning functions, and impaired mechanical cleaning of teeth and mucous membranes. These changes create favorable conditions for the accumulation of food debris and the formation of dental plaque, which, in turn, promotes the proliferation of acidogenic microflora and contributes to oral dysbiosis. Such a disturbed microbiological balance is a leading factor in the development of caries and inflammatory periodontal diseases in children. Prolonged dysbiosis and chronic periodontal inflammation, in turn, can deepen existing malocclusion, contribute to pathological tooth displacements, and complicate orthodontic treatment, jeopardizing the stability of its results. Despite a significant number of studies devoted to individual aspects of distal occlusion, breathing disorders, and periodontal pathology, a comprehensive analysis of the interrelationships among these conditions at the clinical, functional, microbiological, and immunological levels remains underexplored. It is essential to clarify the pathogenetic mechanisms underlying their combination and, on this basis, to develop a substantiated interdisciplinary approach to diagnosis and treatment in children. This will allow for early detection of functional disorders and effective prevention of associated complications, ensuring the harmonious development of the dentoalveolar system and the child’s overall health. Aim of the Study. To investigate the interrelationships between physicochemical and biochemical parameters of oral fluid (pH, salivary flow rate and volume, viscosity, total protein, lysozyme activity) and periodontal pathology in children with distal occlusion and associated impaired respiratory function, and to substantiate an interdisciplinary approach to their diagnosis, treatment, and prevention. Materials and Methods. The study was a prospective, controlled cohort study aimed at investigating the interrelationships among microbiological and immunological parameters and periodontal pathology in children with distal occlusion and impaired respiratory function. The study involved 167 children aged 6 to 14 years with diagnosed distal occlusion, who were divided into two age groups: Group I (n = 88)—children aged 6–9 years; Group II (n = 79)—children aged 10–14 years. For comparative analysis, control subgroups were formed in both age categories, comprising 15 children each with no malocclusion, periodontal pathology, or respiratory dysfunction. Periodontal tissue pathology was detected in 42 children (47.7%) in Group I and 45 children (60%) in Group II. An analysis of the physicochemical and biochemical parameters of oral fluid (OF) was conducted. Results. The study revealed significant changes in oral fluid (OF) parameters in children with distal occlusion (DO), especially in the presence of concomitant periodontal pathology and breathing disorders. A decrease in pH was observed: in the younger group to 6.5 ± 0.2 (compared to 7.0 ± 0.1 in the control), and in the older group to 6.4 ± 0.2 (compared to 7.3 ± 0.2 in the control). A decrease in volume (to 1.0 ± 0.2 mL/h) and salivary flow rate (to 0.15 ± 0.03 mL/min) was also noted in both age groups. Concurrently, an increase in viscosity was recorded: 1.5 ± 0.2 conventional units in the younger group and 1.6 ± 0.2 traditional units in the older group. The total protein concentration also increased: to 1.3 ± 0.3 mg/mL in the younger group and to 1.4 ± 0.3 mg/mL in the older group. At the same time, lysozyme activity was decreased to 12.0 ± 3.3 µg/mL in the younger group and to 11.1 ± 3.3 µg/mL in the older group. These data indicate a weakening of local protection and an increase in inflammation, which progresses with age. Conclusion. The results underscore the need for a comprehensive interdisciplinary approach to the diagnosis and treatment of distal occlusal disease in children, including correction of respiratory function and periodontal status to prevent the progression of pathology.